Konflik Komunikasi Peran Ganda (Double Burden) Perempuan (Studi Kasus : Masyarakat Desa Sumber Melati Diski Kabupaten Deli Serdang) - Nurhaliza, Sofia; Achiriah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The double role (double burden) for women has many communication conflicts, with several parties supporting and those opposing, this often occurs in society. A number of people think that double burden women are allowed as long as they do not violate their nature as women. However, a number of people feel worried because in many cases double burden women are often unable to balance their roles between being at home and outside the home, namely work. which will result in failure in one of these positions, or even both. An incident that arises in society is that women tend to earn a living more actively to earn additional money for the family and to express their own desires. A woman who has these two roles is defined as a woman who has two positions, namely being a housewife and a working woman. This research was conducted to find out how multiple role communication conflicts occur in women. Qualitative research methods, carried out through in-depth interviews, are used to understand the problem being studied. In terms of communication conflict, it was found that the lack of communication provided by a woman caused conflict. It can be concluded that the dual role accepted by a woman is a burden for some women.